Happiness Index in Physiotherapy Students of Gujarat, India: A Cross-sectional Study - Shivani Sheth; Jainil Trivedi; Megha Sheth (Journal of Integrated Health Sciences)
Introduction: Happiness, a mental feeling of well-being, is an important trait for a person to function with greater productivity. In undergraduate students, the psychological status can greatly impair academic outcomes. Aim: This study is aimed at evaluating overall happiness among physiotherapy students Material and Methods: A cross-sectional study was conducted to assess the happiness index in physiotherapy students of Gujarat, India. One hundred and three physiotherapy students aged 18–25 years filled the Oxford Happiness Questionnaire, which was used to evaluate their happiness index. Data analysis was done using Excel. Results: The mean happiness index score was 2.6 across 103 participants where 24.3% were males and 75.7% were females. Conclusion: The physiotherapy students of Gujarat, IN are somewhat unhappy.